Circulating DNA: diagnostic tool and predictive marker for overall survival of NSCLC patients. - Raquel Catarino (Public Library of Science (PLoS), 2012)
Purpose The purpose of our study was to determine whether the amounts of circulating DNA (cDNA) could discriminate between NSCLC patients and healthy individuals and assess its value as a prognostic marker of this disease. Methods We conducted a study of 309 individuals and the cDNA levels were assessed through real-time PCR methodology. Results We found increased cDNA levels in NSCLC patients compared to control individuals. We also found a decreased overall survival time in patients presenting high cDNA levels, when compared to lower cDNA concentrations. Conclusions Quantification of cDNA may be a good tool for NSCLC detection with potential for clinical applicability.